2022
DOI: 10.3389/fpsyg.2022.964313
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress of adolescents during the COVID-19 lockdown: Bayesian multilevel modeling of the Czech HBSC lockdown survey

Abstract: ObjectiveLong-term isolation, including lockdowns and quarantines, may have a distressing effect on anyone experiencing it. Adolescent brain architecture is very sensitive to environmental adversities, and the mental health development of adolescents may be particularly vulnerable during the pandemic era. In order to better understand the triggers for perceived adolescent stress (PSS) during the COVID-19 lockdown, the present study aimed to assess the effects of social well-being and changes in time use during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…In addition, different groups are disproportionally affected by the pandemic restrictions due to other life events; for instance, young adults graduating from school and moving out of town during the COVID-19 pandemic may have limited opportunities to meet new people or may have limited ability to spend a year abroad. Different studies observed that increased feelings of loneliness within groups of adolescents and young adults were strongly associated with higher levels of depression and anxiety during the pandemic 9,13,16,44 . Furthermore, Tetreault et al stated that more disruptions in daily life as well as school and extracurricular activities were associated with increased symptoms of anxiety and depression 4 .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, different groups are disproportionally affected by the pandemic restrictions due to other life events; for instance, young adults graduating from school and moving out of town during the COVID-19 pandemic may have limited opportunities to meet new people or may have limited ability to spend a year abroad. Different studies observed that increased feelings of loneliness within groups of adolescents and young adults were strongly associated with higher levels of depression and anxiety during the pandemic 9,13,16,44 . Furthermore, Tetreault et al stated that more disruptions in daily life as well as school and extracurricular activities were associated with increased symptoms of anxiety and depression 4 .…”
Section: Discussionmentioning
confidence: 98%
“…A study on adolescents and their perceived stress in the Czech Republic concluded that girls are more affected by lockdowns. The strongest predictor was loneliness, while having someone to talk to, scored the lowest [ 46 ]. Garbóczy et al reported elevated perceived stress levels and health anxiety in 1289 Hungarian and international students, also affected by disengagement from home and inadequate coping strategies [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents appear to be more sensitive to the effects of COVID-19 than adults in developing internalizing and externalizing symptoms such as anxiety, depression, irritability and sleep problems [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%